2018
DOI: 10.1007/s10236-018-1139-7
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami detection by high-frequency radar in British Columbia: performance assessment of the time-correlation algorithm for synthetic and real events

Abstract: The authors recently proposed a new method for detecting tsunamis using High-Frequency (HF) radar observations, referred to as "Time-Correlation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…One promising avenue for early detection of tsunamis from such non-seismic sources is the use of shore-based high frequency radars, combined with tsunami detection algorithms based on simulations of potential tsunami scenarios cf. 53 , and literature reviews therein. Following the premonitory study of 12 , the present research confirms that state-of-the-art numerical models can accurately simulate the potential hazard from volcanic induced tsunamis.…”
Section: Discussionmentioning
confidence: 99%
“…One promising avenue for early detection of tsunamis from such non-seismic sources is the use of shore-based high frequency radars, combined with tsunami detection algorithms based on simulations of potential tsunami scenarios cf. 53 , and literature reviews therein. Following the premonitory study of 12 , the present research confirms that state-of-the-art numerical models can accurately simulate the potential hazard from volcanic induced tsunamis.…”
Section: Discussionmentioning
confidence: 99%
“…These storms were the remnants of Typhoon Songda, thus the triggering event was atmospheric in origin and there was no seismic alert issued at that time. An in-depth a posteriori analysis of the meteorological data gathered during the event, together with the recorded HF radar data in the light of an improved tsunami detection algorithm, clearly showed that two successive abnormal long waves impacted the coast, which was a meteotsunami (Guérin et al, 2018). This tsunami was first detected by the HFR 60 km offshore, about 45 min before its arrival on the coast.…”
Section: Hazard Detectionmentioning
confidence: 95%
“…The Japan tsunami was detected 15-19 min before its arrival at the coast. Grilii et al [14] and Guérin et al [15] proposed a detection method using cross-correlation of the signals received at two points along a tsunami wave ray calculated beforehand and reported detection beyond the continental shelf, based on numerical experiments for far-and near-field tsunamis. The usage of band-averaged velocities is effective for detecting an incoming tsunami by reducing the observed errors in radial velocities and extracting the coherent motions of surface waters.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are some difficulties in determining the value of the q-factor beforehand, which varies with the bottom topography and tsunami magnitude, and in applying the method to a region with a complex bottom topography when the area-band-averaged velocities are used for tsunami arrival detection. For the signal-based method, it is necessary to calculate the tsunami wave rays beforehand, and the performance depends on the selection of rays and the choice of low-and high-contrast threshold values (Guérin et al [15]). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation